PROTOTYPE AUGMENTED REALITY BERBASIS FACE RECOGNITION PADA SMARTPHONE ANDROID UNTUK PENGENALAN WAJAH MAHASISWA JTETI UGM - , M. IBNU FADHL BAGUS BASUKI, Ir. Rudy Hartanto, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Face is an identity of a person which always brought by that same person. Compared by an identity card, face forgery is much difficult than identity card forgery. Which is why, a fast and accurate identification using face recognition need to be applied, both for increasing security and make people identification much easier. Face recognition is a process of identifying a face from a person who has been stored in a database/been trained before. In 90âs, face recognition technologies were developing rapidly as the demand was also increasing from the world. Those increased demand was then affecting the improvement of the methods of face recognition which now grow rapidly and vary. Two of the popular methods are Haar and LBP (Local Binary Pattern). Augmented reality is a way to show entities that only reside in digital world to be appeared in reality. Augmented reality is often used in purposes of entertainment, informational, monitoring, etc. This research is focused on the making of a prototype of a software of augmented reality based face detection using Haar and LBP and face recognition using LBP in smartphone Android.